Long, tall Christmas - Dailey, Janet (Kensington Books, 2015)
Resisting her feelings for horse whisperer Sky Fletcher before dangerous complications in her privileged life threaten her survival, Lauren Prescott is enmeshed in a conspiracy that threatens to expose her protector's secret family ties.